Evaluation of Brittle Rice Straw as a Novel Roughage Resource for Enhancing the Performance of Holstein Cows - Phonkompaeng, Amonrat; Boonchu, Purich; Sawasdee, Anuchart; Rangubhet, K. Teepalak; Kongmun, Phongthorn; Dhital, Bigya; Pudasaini, Rameshwor; Wang, Chang‐Sheng; Chiang, Hsin‐I (Animal science journal, 2025)
This study evaluated the straw of brittle mutant rice ( Oryza sativa L.) as an alternative forage for dairy cows. In vitro incubation was conducted to investigate nutrient digestibility in Bermuda hay (BH), wild‐type (WT), purple brittle (PB), and green brittle (GB) rice straws. After in vitro analysis, three treatment diets including (i) diet 100% BH, (ii) diet 25% WT (mixed 75% BH), and (iii) diet 25% GB (mixed 75% BH) were used in a feeding trial for Holstein cows. After 48‐h in vitro incubation, both brittle straw varieties showed higher dry matter (DM) digestibility than the WT ( p < 0.05) and similar to BH. GB and BH showed higher crude protein (CP) digestibility than other treatments ( p < 0.05) with no significant difference in neutral detergent fiber (NDF) digestibility. The in situ analysis revealed that the 25% GB diet demonstrated superior DM and CP digestibility compared to the 25% WT diet. Including 25% GB in diets significantly ( p < 0.05) improved rumination time but had no significant effect on daily DM intake or ruminal pH, although ruminal ammonia nitrogen concentrations tended to decrease. These results suggest that brittle rice straw varieties could be potential alternative forages for dairy cows.